Opportunistic bone density assessment using pre-treatment [18F]FDG-PET/CT identifies fracture risk in lymphoma patients undergoing corticosteroid-containing chemotherapy - Genevieve Douglas; Kane M. Nicholls; Erin Paul; Zoe Loh; Sze-Ting Lee; Kathryn L Hackman; Cherie Chiang; Niamh Waters; Geoffrey Chong; Ashvind Prabahran; Eliza A. Hawkes (Haematologica)
Not available.